The neural coding of expected and unexpected monetary performance outcomes: Dissociations between active and observational learning - Bellebaum, C.; Jokisch, D.; Gizewski, E.R.; Forsting, M.; Daum, I. (Behavioural brain research, 2012)
► Learning performance is similar for active and observational feedback learning. ► The anterior caudate nucleus is activated more strongly for active learning. ► The medial orbitofrontal cortex is activated more strongly for active learning. ► Hippocampal activity is enhanced for unexpected reward in observational learners. Successful adaptation to the environment requires the learning of stimulus–response–outcome associations. Such associations can be learned actively by trial and error or by observing the behaviour and accompanying outcomes in other persons. The present study investigated similarities and differences in the neural mechanisms of active and observational learning from monetary feedback using functional magnetic resonance imaging. Two groups of 15 subjects each – active and observational learners – participated in the experiment. On every trial, active learners chose between two stimuli and received monetary feedback. Each observational learner observed the choices and outcomes of one active learner. Learning performance as assessed via active test trials without feedback was comparable between groups. Different activation patterns were observed for the processing of unexpected vs. expected monetary feedback in active and observational learners, particularly for positive outcomes. Activity for unexpected vs. expected reward was stronger in the right striatum in active learning, while activity in the hippocampus was bilaterally enhanced in observational and reduced in active learning. Modulation of activity by prediction error (PE) magnitude was observed in the right putamen in both types of learning, whereas PE related activations in the right anterior caudate nucleus and in the medial orbitofrontal cortex were stronger for active learning. The striatum and orbitofrontal cortex thus appear to link reward stimuli to own behavioural reactions and are less strongly involved when the behavioural outcome refers to another person's action. Alternative explanations such as differences in reward value between active and observational learning are also discussed.